The impact of human-induced environmental destruction on destination image perception and travel behaviour: The case of Australia's Great Barrier Reef. (January 2017) - Salvatierra, Javier; Walters, Gabrielle
The study presented in this article provides a valuable insight into the impact of human-induced environmental destruction on the travel market's image perceptions of a World Heritage-listed tourism icon: the Great Barrier Reef (GBR). The study employs a pre-/post-experimental design to explore how tourists are likely to respond to the media hype surrounding the construction of a port terminal, known as the Abbot Point Project, which will inevitably have some perceived environmental consequence for the ecological sustainability of a section of the GBR. We measured the change in respondents' image perceptions and travel intentions as a result of their exposure to information about the Abbott Point Project and explored how existing knowledge, past experience and demographic background may influence this change. The findings reveal a significant change in tourists' perceptions concerning Australia's conservation efforts towards the GBR, and consequently a change is noted in terms of the time frame in which tourists intend to visit the icon. The results of this study provide valuable information for destination managers responsible for marketing the GBR and other destinations subject to human-induced, and often controversial, environmental destruction.